Analisis Penggunaan Kata Baku dan Tidak Baku Dalam Media Sosial - Parulian Sibuea; Anisa Dwi Kiswati; Dwi Riyanti (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
Language is a national identity used in interaction. Humans need language as a means of communication. Language is very important for human communication because through it they can interact and talk about anything. Almost every region in Indonesia uses its language in various aspects of life. To be a good, correct and easy to understand language, a unified language must have a clear structure and standard words. Indonesian is the official language of our country, Indonesia. With advances in information technology, people can communicate so quickly throughout the world, spanning countries and continents. This research aims to find out how many social media users still use Indonesian incorrectly.